2017
DOI: 10.1002/slct.201701411
|View full text |Cite
|
Sign up to set email alerts
|

Short Naphthalene Organophosphonate Linkers to Microporous Frameworks

Abstract: We report two novel 3D porous metal‐organophosphonate metal organic frameworks (MOFs) [{Cu(4, 4’‐bpy)0.5(1,4‐NDPA‐H2)] (1), [{Cu2(4,4’‐bpy)0.5}(1,4‐NDPA)] (2) and a non‐porous [{Cu(4, 4’‐bpy)}(2,6‐NDPA‐H2)] (3) constructed using the structurally rigid 1,4‐naphthalenediphosphonic acid (1,4‐NDPA‐H4) and 2,6‐naphthalenediphosphonic acid (2,6‐NDPA‐H4). 1 and 2 exhibit high surface areas obtained using the structurally rigid and short aromatic organophosphonate linkers with copper. The compound 1 has been further a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…The same chain pattern was also observed in structurally rigid naphthalene arylphosphonate linkers with square pyramidal and octahedral metal atoms producing microporous frameworks. 29 The stability of such edge shared Zn 2 P 2 O 4 chains is significant as robust inorganic building units for future metal organophosphonate compounds, which could hypothetically produce isoreticularly expanding void channels with tetratopic, tritopic and ditopic ligands with expanding tether lengths. As seen in the thermogravimetric analysis graphic (see ESI †), the compound is an unusually stable MOF as organic components from MTPPA start decomposing at ca.…”
Section: àmentioning
confidence: 99%
“…The same chain pattern was also observed in structurally rigid naphthalene arylphosphonate linkers with square pyramidal and octahedral metal atoms producing microporous frameworks. 29 The stability of such edge shared Zn 2 P 2 O 4 chains is significant as robust inorganic building units for future metal organophosphonate compounds, which could hypothetically produce isoreticularly expanding void channels with tetratopic, tritopic and ditopic ligands with expanding tether lengths. As seen in the thermogravimetric analysis graphic (see ESI †), the compound is an unusually stable MOF as organic components from MTPPA start decomposing at ca.…”
Section: àmentioning
confidence: 99%
“…Our recent research effortsw itha rylphosphonic acid synthesis have generated novel strategies to introduce phosphonic acid arounda romatic scaffolds, by Suzuki cross coupling or the d-catalyzed Arbuzov reaction. [44][45][46][47] For this study,a ss een in Scheme1,w Information for detailed synthesis) . Ap revious synthesis of p-H 8 TPPA relied on the Ni-catalyzed Arbuzov reaction.…”
mentioning
confidence: 99%
“…[ 30,33–36 ] Recently, Yücesan and co‐workers synthesized the phosphonate MOF TUB75 (where TUB stands for Technische Universität Berlin) at temperatures above 180 °C and under hydrothermal reaction conditions. [ 38 ] The crystal structure revealed that this MOF contains 1D copper dimer chains linked by polyaromatic 1,4‐naphthalenediphosphonic acid linkers (see Figure ). This chain structure is unique compared to that of previously reported 1D IBUs in the literature with respect to the presence of three different (and relatively short) characteristic Cu–Cu distances along the 1D IBU (see Figure 1B).…”
Section: Figurementioning
confidence: 99%
“…[ 38 ] The thermal decomposition patterns of phosphonate MOFs constructed using 4,4′‐bipyridine as the auxiliary linker with 1,4‐naphthalenediphosphonic acid, 2,6‐naphthalendiphosphonic acid, and different aromatic phosphonic acids were also previously reported. [ 38,39 ] MOFs in this family have a general tendency to be thermally stable up to ≈375 °C, after which thermal decomposition begins. In our previous work with 2,6‐naphthalendiphosphonic acid, we found that removing the 4,4′‐bipyridines to obtain pure metal phosphonates increases the thermal stability to ≈400 °C.…”
Section: Figurementioning
confidence: 99%